2018
DOI: 10.3390/ijerph15081689
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Condom Use among Undergraduate Students Based on the Theory of Planned Behaviour, Coquimbo, Chile, 2016

Abstract: Background: Sexually transmitted infections and pregnancy in adolescents are acknowledged public health problems in many countries. Although it is known that the proper use of condoms allows avoiding these health problems, their use in Chile is still limited, for unknown reasons. Objective: Based on planned behavioural theory, the aim was to validate a behaviour model regarding condom use by measuring the influence of the variables that predict this use among Chilean university students. Methods: A cross-secti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
11
1
Order By: Relevance
“…Consequently, we could not compare our results with those of other studies. Outside South Korea, three studies showed that attitude was a predictor of condom use intentions, but not of tangible condom-use behaviors (Ramírez-Correa & Ramírez-Santana, 2018;Teye-Kwadjo, Kagee, & Swart, 2017). Given that there are limited studies related to our speci c predictors, further research should be conducted to establish the relevance of condom-use behaviors to con rm our results.…”
Section: Discussionmentioning
confidence: 72%
“…Consequently, we could not compare our results with those of other studies. Outside South Korea, three studies showed that attitude was a predictor of condom use intentions, but not of tangible condom-use behaviors (Ramírez-Correa & Ramírez-Santana, 2018;Teye-Kwadjo, Kagee, & Swart, 2017). Given that there are limited studies related to our speci c predictors, further research should be conducted to establish the relevance of condom-use behaviors to con rm our results.…”
Section: Discussionmentioning
confidence: 72%
“…However, is coffee a healthy product? Some authors have made meta-analyses of observational and interventional studies of coffee consumption and health outcome [23]. They concluded that coffee drinking seems commonly safe within general levels of consumption, most suggesting a substantial risk reduction for several health outcomes at three to four cups a day, and more likely to do good to health than damage it.…”
Section: Specialty Coffeementioning
confidence: 99%
“…They concluded that coffee drinking seems commonly safe within general levels of consumption, most suggesting a substantial risk reduction for several health outcomes at three to four cups a day, and more likely to do good to health than damage it. Nevertheless, coffee experiences a chemical transformation from the unroasted green bean, and the type of bean, degree of roasting, and preparation procedure including coffee grind setting and brew type all impact on the biochemical composition of the final drink [23].…”
Section: Specialty Coffeementioning
confidence: 99%
“…TPB has been widely used in several research topics. Recently, TPB has been used as a basis in studies on social phenomena in Latin America as examples to explain the intention to adopt electronic commerce by SMEs [28], to predict the purchase of products [29], and in the modelling of behaviours associated with public health, such as condom use [30] and telemedicine [31,32]. In these TPB applications, the behavioural intention is explained in a range from 35 to 85%, depending on the phenomenon studied.…”
Section: Introductionmentioning
confidence: 99%